All optical Q-switched laser based spiking neuron - Mekemeza-Ona, Keshia; Routier, Baptiste; Charbonnier, Benoît (Frontiers in Physics, 2022)
This paper studies theoretically the use of a Q-switch laser with side light injection as a spiking all-optical neuron for photonic spiking neural networks (PSNN). Ordinary differential equations for the multi-section laser are presented, including terms for the side light injection for gain quenching and saturable absorption. The behaviour of the laser mimics that of a spiking neuron with ultrafast pico-second scale response and low power control signals.